2020
DOI: 10.3389/fnins.2020.614643
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of Immunomodulators: A Ray of Hope for Alzheimer’s Disease?

Abstract: Alzheimer’s disease (AD) is the most common age-related neurodegenerative disorder characterized by cognitive decline and by the presence of amyloid β plaques and neurofibrillary tangles in the brain. Despite recent advances in understanding its pathophysiological mechanisms, to date, there are no disease-modifying therapeutic options, to slow or halt the evolution of neurodegenerative processes in AD. Current pharmacological treatments only transiently mitigate the severity of symptoms, with modest or null ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 134 publications
1
13
0
Order By: Relevance
“…Thus, we need new treatments targeting other pathomechanisms of the disease such as the neuroinflammation. 265 , 266 …”
Section: What About Interventions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we need new treatments targeting other pathomechanisms of the disease such as the neuroinflammation. 265 , 266 …”
Section: What About Interventions?mentioning
confidence: 99%
“…Some immunomodulating agents may also be considered for AD treatment. 266 Copaxone used in multiple sclerosis to boost the T cell immune response could modulate the microglia response. 355 Rapamycin, an mTOR inhibitor used as anti-aging drug, could be considered as an immunomodulatory drug in case of AD as preclinical data showed that it can maintain BBB integrity and decrease Aβ pathology.…”
Section: Reinforcement Of the Antimicrobial Defense By Stimulating The Immune System (Immunomodulation)mentioning
confidence: 99%
“…Recent evidence suggests that changes in peripheral and central adaptive immunity occur in AD patients. Nevertheless, anti-inflammatory drugs have produced disappointing results in AD treatment [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, dimethyl fumarate, an immunomodulatory compound used to treat multiple sclerosis, seems to have neuroprotective effects, reducing neuroinflammation and improving cognitive performance in rats infused with streptozotocin ( Majkutewicz et al, 2016 ). Currently, several immune-oncological and anti-TNF-α compounds are under preclinical and clinical investigation as neuroprotectants in AD, as elegantly reviewed elsewhere in this issue ( Munafò et al, 2020 ). Of note, recent preclinical data have shown that a checkpoint inhibitor against the programmed death-1 (PD-1) protein, clinically used in cancer immunotherapy, resulted in improved clearance of cerebral Aβ plaques and cognitive performance in an animal model of AD ( Baruch et al, 2016 ).…”
Section: Neuroinflammation In Neurological Disordersmentioning
confidence: 99%